Hospital Resource Utilization and Presence of Advance Directives at the End of Life for Adults with Congenital Heart Disease - Steiner, Jill M. (Congenit Heart Dis, 2018)
OBJECTIVE: Overall healthcare resource utilization by adults with congenital heart disease has increased dramatically in the last two decades, yet little is known about utilization patterns at the end of life. The objective of this study is to better understand the patterns and influences on end-of-life care intensity for adults with congenital heart disease. METHODS: We identified a sample of adults with congenital heart disease (n=65), cancer (n=10,784), or heart failure (n=3,809) who died between January 2010 and December 2015, cared for in one multi-hospital healthcare system. We used multivariate analysis to evaluate markers of resource utilization, location of death, and documentation of advance care planning among patients with congenital heart disease versus those with cancer and those with heart failure. RESULTS: Approximately 40% of adults with congenital heart disease experienced inpatient and intensive care unit hospitalizations in the last 30 days of life; 64% died in the hospital. Compared to patients with cancer, patients with ACHD were more likely to have inpatient (adjusted risk ratio 1.57; 95% CI 1.12–2.18) and intensive care unit admissions in the last 30 days of life (adjusted risk ratio 2.56; 95% CI 1.83–3.61), more likely to die in the hospital (adjusted risk ratio 1.75; 95% CI 1.43–2.13), and more likely to have documentation of advance care planning (adjusted risk ratio 1.46; 95% CI 1.09–1.96). Compared to patients with HF, patients with ACHD were less likely to have an intensive care unit admission in the last 30 days of life (adjusted risk ratio 0.73; 95% CI 0.54–0.99). CONCLUSIONS: Adults with congenital heart disease have significant hospital resource utilization near the end of life compared to patients with cancer, notable for more hospitalizations and a higher likelihood of death in the hospital. This population represents an important opportunity for the application of palliative and supportive care.